Investigation of residual stresses measured during laser surface modification of tantalum coated steel substrates - A. Bharatish; G. N. Vijayakumara; B. Venkataraman; G. Satheesh Babu; D. V. N. Harish; Sivakumar Solaiachari; Temel Varol (Cogent Engineering)
This study investigates the influence of laser pulse energy and scanning speed on the residual stresses induced during the laser surface treatment of tantalum-coated SS461 steel substrates. Residual stress simulations were performed using the COMSOL Multiphysics package and validated against experimental measurements obtained through X-ray diffraction (XRD). The surface morphology of the Ta-coated steel substrates was analyzed using scanning electron microscopy (SEM). It was found that a combination of low pulse energy and moderate scanning speed resulted in compressive residual stress of 0.66 GPa in the Ta coating, which is 21.4% lower than the 0.84 GPa stress induced during the sputtering process. Increasing pulse energy shifted residual stress from compressive to tensile, while higher scanning speed decreased stress magnitude, likely due to reduced β-Ta phase. The laser-treated surfaces were characterized by smooth splats, microcracks, and dendritic structures, which contributed to the failure of the coating. Thus the study provided valuable insights into the optimization of laser surface treatment parameters for improving the performance of tantalum coatings on steel substrates.